The development of science process skills in visually impaired students: analysis of the activities - Aydın Kızılaslan (International Journal of Evaluation and Research in Education (IJERE), 2019)
Students with visual impairments face tremendous challenges in daily life while learning life skills as they do not have the benefit of visual cues. The skills that visually impaired students are expected to learn include not only everyday life skills, but also scientific process skills too. In this study, case study was used to develop an instructional design to teaching science concepts to visually impaired students. The aim of this study is to analyze the efficacy of science activities of this developed instructional design. The study consists of three basic stages. In the first stage, visually impaired students’ learning needs are identified. In the second stage teaching materials and activities are designed and developed. In the last stage, these activities were analyzed in terms of scientific process skills through observation forms. As a result, most of the developed activities are suited for development of the scientific process skills.